2007
DOI: 10.1021/ja068849o
|View full text |Cite
|
Sign up to set email alerts
|

Role of Aromatic Side Chains in the Folding and Thermodynamic Stability of Integral Membrane Proteins

Abstract: Aromatic residues are frequently found in helical and beta-barrel integral membrane proteins enriched at the membrane-water interface. Although the importance of these residues in membrane protein folding has been rationalized by thermodynamic partition measurements using peptide model systems, their contribution to the stability of bona fide membrane proteins has never been demonstrated. Here, we have investigated the contribution of interfacial aromatic residues to the thermodynamic stability of the beta-bar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
210
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 157 publications
(225 citation statements)
references
References 42 publications
(79 reference statements)
13
210
2
Order By: Relevance
“…In addition to stabilizing the concentration of monomer in aqueous solutions, inclusion of any C-terminal aromatic residue provided a lipid/water interfacial anchor. As was seen with W, F residues are commonly present (and Y to a lesser extent) at the hydrophobic/hydrophilic interface for TM segments of membrane proteins (Braun and von Heijne, 1999;Mall et al, 2000;Demmers et al, 2001;de Planque et al, 2003;Granseth et al, 2005;van der Wel et al, 2007;Hong et al, 2007 Comparing all of the summarized data in Tables 3 and 4 and the profiles shown in Figs. 16 and 17, the sequences displaying the highest ion transport activity and the second and third most left-shifted k 1/2 values are both W containing peptide sequences, NK 4 -M2GlyR-p22 T19R, S22W and NK 4 -M2GlyR-p22 Q21W, S22R.…”
Section: Wt S22wmentioning
confidence: 55%
See 1 more Smart Citation
“…In addition to stabilizing the concentration of monomer in aqueous solutions, inclusion of any C-terminal aromatic residue provided a lipid/water interfacial anchor. As was seen with W, F residues are commonly present (and Y to a lesser extent) at the hydrophobic/hydrophilic interface for TM segments of membrane proteins (Braun and von Heijne, 1999;Mall et al, 2000;Demmers et al, 2001;de Planque et al, 2003;Granseth et al, 2005;van der Wel et al, 2007;Hong et al, 2007 Comparing all of the summarized data in Tables 3 and 4 and the profiles shown in Figs. 16 and 17, the sequences displaying the highest ion transport activity and the second and third most left-shifted k 1/2 values are both W containing peptide sequences, NK 4 -M2GlyR-p22 T19R, S22W and NK 4 -M2GlyR-p22 Q21W, S22R.…”
Section: Wt S22wmentioning
confidence: 55%
“…A propensity for tryptophans residing at the aqueous/lipid interface also had been observed and tested by others (Braun and von Heijne, 1999;Mall et al, 2000;Demmers et al, 2001;de Planque et al, 2003;Granseth et al, 2005;van der Wel et al, 2007;Hong et al, 2007). Placing a W at the Cterminus sets the registry of the TM segment that spans the bilayer.…”
Section: M2glyr Studiesmentioning
confidence: 90%
“…For example, tyrosine has been thought to be a particularly suitable amino acid for β-barrel aromatic girdles. Its amphiphilic character is ideal for the interfacial environment, it is statistically overrepresented and highly conserved in aromatic girdles, and it has been experimentally observed to make a larger contribution to β-barrel stability than would be predicted from hydrophobicity scales (59). In natural β-barrels, tyrosine is predominantly found at the C-terminal ends of β-strands (60); at this end the available χ 1 dihedral angles better position the sidechain to "snorkel" into the lipid headgroup region.…”
Section: Discussionmentioning
confidence: 99%
“…The structure contains two aromatic side chains, Phe 9 and Trp 14 , that point toward each other in the kink region and that face the hydrophobic interior of the lipid membrane (3). Because aromatic side chains are well known to anchor membrane proteins in the membrane interface (16,17), it was reasonable to hypothesize that Phe 9 and Trp 14 would also stabilize the active conformation of the HA fusion domain in membranes. However, recent data were not entirely consistent with this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, additional factors must contribute to the formation of the active boomerang conformation of the HA fusion domain in membranes. Trp contributes Ϫ2.0 kcal/mol more energy to the stability of membrane proteins than Ala, but Phe contributes only Ϫ1.2 kcal/mol more (17,18). Because Ile 10 is located right next to Phe 9 in the hydrophobic pocket of the boomerang structure (3) and because Ile is expected to contribute another Ϫ0.5 kcal/mol over Ala (18), we suspected that both Phe 9 and Ile 10 were needed to stabilize the N-terminal arm of the boomerang structure in the membrane interface.…”
Section: Discussionmentioning
confidence: 99%